Security Analysis of eIDAS -- The Cross-Country Authentication Scheme in Europe - Engelbertz, Nils; Erinola, Nurullah; Herring, David; Somorovsky, Juraj; Mladenov, Vladislav; Schwenk, Jörg (12th USENIX Workshop on Offensive Technologies (WOOT 18))

Modelling the Interface of Hybrid Metal-FRP Components Joint by Form Closures - Triebus, Marcel; Tröster, Thomas; Camberg, Alan Adam; Bienia, S.; Dröder, K. (15. Deutsches LS-Dyna Forum)

The influence of damage accumulation on failure prediction: a comparative assessment of *MAT_224 and *MAT_024 + GISSMO for the application in non-isothermal sheet metal forming - Camberg, Alan Adam; Tröster, Thomas; Schneidt , A.; Sotirov , N.; Tölle, J. (15. Deutsches LS-Dyna Forum)

Controlling nonlinear PDEs using low-dimensional bilinear approximations obtained from data - Peitz, Sebastian (arXiv:1801.06419)
In a recent article, we presented a framework to control nonlinear partial differential equations (PDEs) by means of Koopman operator based reduced models and concepts from switched systems. The main idea was to transform a control system into a set of autonomous systems for which the optimal switching sequence has to be computed. These individual systems can be approximated very efficiently by reduced order models obtained from data, and one can guarantee equality of the full and the reduced objective function under certain assumptions. In this article, we extend these results to continuous control inputs using convex combinations of multiple Koopman operators corresponding to constant controls, which results in a bilinear control system. Although equality of the objectives can be carried over when the PDE depends linearly on the control, we show that this approach is also valid in other scenarios using several flow control examples of varying complexity.

Analyzing high-dimensional time-series data using kernel transfer operator eigenfunctions - Klus, Stefan; Peitz, Sebastian; Schuster, Ingmar (arXiv:1805.10118)
Kernel transfer operators, which can be regarded as approximations of transfer operators such as the Perron-Frobenius or Koopman operator in reproducing kernel Hilbert spaces, are defined in terms of covariance and cross-covariance operators and have been shown to be closely related to the conditional mean embedding framework developed by the machine learning community. The goal of this paper is to show how the dominant eigenfunctions of these operators in combination with gradient-based optimization techniques can be used to detect long-lived coherent patterns in high-dimensional time-series data. The results will be illustrated using video data and a fluid flow example.

Tailored UV Emission by Nonlinear IR Excitation from ZnO Photonic Crystal Nanocavities - Hoffmann, Sandro P.; Albert, Maximilian; Weber, Nils; Sievers, Denis; Förstner, Jens; Zentgraf, Thomas; Meier, Cedrik (ACS Photonics)
Keywords: tet_topic_phc

Erratum: Optical properties of titanium-doped lithium niobate from time-dependent density-functional theory [Phys. Rev. Materials 1, 034401 (2017)] - Friedrich, Michael; Schmidt, Wolf Gero; Schindlmayr, Arno; Sanna, Simone (Physical Review Materials)

Fachsensibilität als Ressource für den Writing Fellow-Ansatz - Frahnert, Vanessa; Karsten, Andrea (Lehren und Lernen mit Writing Fellows. Beiträge zur Forschung, Evaluation und Adaption)
Vanessa Frahnert und Andrea Karsten stellen ihr Textograph*innen-Programm zur Unterstützung des Schreibens in der Lehre vor, das seit dem Sommersemester 2016 zum regelmäßigen Angebot des Kompetenzzentrums Schreiben der Universität Paderborn gehört. Das Programm baut auf den grundlegenden Prinzipien und Überlegungen des Writing Fellow-Konzepts auf, ist aber an die theoretische Ausrichtung des Schreibzentrums sowie die Gegebenheiten der Universität angepasst. Der Beitrag stellt das Programm und seine theoretischen Hintergründe vor und arbeitet die Unterschiede im Vergleich zum Writing Fellow-Ansatz heraus.

Selbstoptimierung - Tönsing, Johanna (Von Automatismen bis Zersetzung. Wörterbuchprojekt des Graduiertenkollegs Automatismen)

Matthäus Merians Paderborn-Darstellung in der ›Topographia Westphaliæ‹. [Laudatio auf Markus Lauert] - Süßmann, Johannes (Neujahrsempfang der Universität Paderborn 21. Januar 2018. Laudationes)

Open Science-Forschung und qualitative Methoden – fünf Ebenen der Reflexion - Steinhardt, Isabel (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Ausgehend von den fünf Schulen von Open Science von Fecher und Friesicke (2014) findet in diesem Beitrag eine Reflexion eines qualitativen Open Science-Forschungsprojektes statt. Mit der Reflexion wird der Offenlegung und Transparenz, die Open Science-Projekten immanent ist, entsprochen. Es soll aber auch zukünftigen Forscherinnen und Forschern, die überlegen ein Open Science Projekt zu starten, dabei helfen mögliche Hürden aber auch Lösungswege zu antizipieren. Als Reflexionsbeispiel dient das Projekt «Nutzung digitaler Medien und Habitus von Studierenden», das auf folgenden fünf Ebenen betrachtet wird: Ebene der Wissensproduktion; Ebene der freien Zugänglichkeit von Wissen; Ebene der Infrastruktur; Ebene der kollaborativen Forschung und Ebene der Impakt-Messung.
Keywords: Mediendidaktik; Hochschule; Open Science

Accelerating Molecular Dynamic Simulations by Offloading Fast Fourier Transformations to FPGA - Ramaswami, Arjun
Molecular Dynamic (MD) simulations are computationally intensive and accelerating them using specialized hardware is a topic of investigation in many studies. One of the routines in the critical path of MD simulations is the three-dimensional Fast Fourier Transformation (FFT3d). The potential in accelerating FFT3d using hardware is usually bound by bandwidth and memory. Therefore, designing a high throughput solution for an FPGA that overcomes this problem is challenging. In this thesis, the feasibility of offloading FFT3d computations to FPGA implemented using OpenCL is investigated. In order to mask the latency in memory access, an FFT3d that overlaps computation with communication is designed. The implementa- tion of this design is synthesized for the Arria 10 GX 1150 FPGA and evaluated with the FFTW benchmark. Analysis shows a better performance using FPGA over CPU for larger FFT sizes, with the 643 FFT showing a 70% improvement in runtime using FPGAs. This FFT3d design is integrated with CP2K to explore the potential in accelerating molecular dynamic simulations. Evaluation of CP2K simulations using FPGA shows a 41% improvement in runtime in FFT3d computations over CPU for larger FFT3d designs.
Keywords: FFT: FPGA; CP2K; OpenCL

Schnittstellenaufgaben im Praxiseinsatz: Aufgabenbeispiel zur „Bleistiftstetigkeit“ und allgemeine Überlegungen zu möglichen Problemen beim Einsatz solcher Aufgaben - Hoffmann, Max (Beiträge zum Mathematikunterricht 2018)

Professionalisierung von Grundschullehrkräften – wissenschaftlich fundiert, praxisorientiert und reflexionsbasiert - Frey, Anne; Buhl, Heike M. (Zeitschrift für Grundschulforschung)
Die Professionalisierung von Grundschullehrkräften mit den speziellen an sie gestellten Anforderungen sowie den Erwartungen der Studierenden bewegt sich zwischen der Notwendigkeit einer wissenschaftlich-konzeptuellen Basis und der Ausrichtung auf die schulische Praxis. Verbindendes Element ist eine gut angeleitete Reflexion. Dieser Dreiklang wird professionstheoretisch begründet, wobei unterschiedliche Ansätze jeweils eigene Impulse für die Lehrerbildung leisten. Vor diesem Hintergrund werden Curricula und hochschuldidaktische Maßnahmen diskutiert. Exemplarisch werden Projekte beschrieben, die in unterschiedlichen Formaten zur Reflexion von Praxis auf theoretischer Basis anregen.
Keywords: Grundschule; Lehrerbildung; Reflexion; Theorie-PraxisVerzahnung; Hochschuldidaktik; Professionstheorie

Intergenerational Transfers: Associations with Adult Children’s Emotional Support of Their Parents - Sommer, Sabrina; Buhl, Heike M. (Journal of Adult Development)
This study investigates how different factors in regard to intergenerational relationships are associated with emotional support given by adults to their parents. The analysis focuses on adult children and their parents in a representative German sample. Data were obtained from the second wave of the German Family Panel (pairfam) consisting of 2064 women and 1841 men. Results show that transfer of emotional support by the adult children was especially associated not only with received emotional support from parents, but also with affection, conflicts, and expectations concerning parents. A moderator analysis focuses on gender and showed differences for the association between given support by adults and conflicts between mothers and fathers. For the offspring, no gender effects were found.
Keywords: Intergenerational relationships; Emotional support; Solidarity; Adult children; Gender

Fallbasierte Modulabschlussprüfungen zur Verzahnung von Theorie und Praxis im Master des Lehramtsstudiums - Buhl, Heike M.; Bohndick, Carla; Bonanati, Sabrina; Greiner, Christian; Hilkenmeier, Johanna; Kordts-Freudinger, Robert (Psychologiedidaktik und Evaluation XII)

Externe und interne Qualitätssicherung von Studium und Lehre durch Akkreditierungs- und Evaluationsverfahren - Steinhardt, Isabel; Schneijderberg, Christian; Krücken, Georg; Baumann, Janosch
Mit diesem Working Paper werden die wesentlichen Ergebnisse des INCHER-Forschungsprojekts „Externe und interne Qualitätssicherung von Studium und Lehre durch Akkreditierungs- und Evaluationsverfahren“ (kurz EIQSL) zusammengefasst. Dabei ging es um die Rekonstruktion und Einordnung der externen Qualitätssicherung im Rahmen der allgemeinen hochschulpolitischen Governance, das vielschichtige Qualitätsverständnis, das den Verfahren der Qualitätssicherung unterliegt, die hochschulinternen Prozesse und Strukturen der Qualitätssicherung, die Besonderheiten des Peer Reviews in Akkreditierungsverfahren sowie das komplexe Verhältnis zentraler Akteure zueinander. Zusammenfassend zeigte sich – über die Detailergebnisse hinaus –, dass die externe Qualitätssicherung an Hochschulen durch Akkreditierung nach wie vor umstritten ist. Die theoretisch auf der Grundlage des Neo-Institutionalismus und der Systemtheorie begründete Erwartung der Autoren, dass sich Institutionalisierungsprozesse aufzeigen lassen, die zu einer schrittweisen, im Zeitverlauf beobachtbaren „Normalisierung“ führen, wurde nicht erfüllt. Zusätzlich ist nicht nur die Legitimation des Systems kontrovers und umstritten, sondern auch die seiner Effekte. Es zeigten sich unterschiedliche, teils positiv, teils negativ bewertete Effekte, die sich - will man nicht unzulässig verallgemeinern - nicht zu einer wissenschaftlichen Gesamteinschätzung aggregieren lassen.

Semantic Data Mediator: Linking Services to Websites - Wolters, Dennis; Heindorf, Stefan; Kirchhoff, Jonas; Engels, Gregor (Service-Oriented Computing -- ICSOC 2017 Workshops)
Many websites offer links to social media sites for convenient content sharing. Unfortunately, those sharing capabilities are quite restricted and it is seldom possible to share content with other services, like those provided by a user's favorite applications or smart devices. In this paper, we present Semantic Data Mediator (SDM) --- a flexible middleware linking a vast number of services to millions of websites. Based on reusable repositories of service descriptions defined by the crowd, users can easily fill a personal registry with their favorite services, which can then be linked to websites by SDM. For this, SDM leverages semantic data, which is already available on millions of websites due to search engine optimization. Further support for our approach from website or service developers is not required. To enable the use of a broad range of services, data conversion services are automatically composed by SDM to transform data according to the needs of the different services. In addition to linking web services, various service adapters allow services of applications and smart devices to be linked as well. We have fully implemented our approach and present a real-world case study demonstrating its feasibility and usefulness.

Supporting the Cognitive Process in Annotation Tasks - Seemann, Nina; Geierhos, Michaela; Merten, Marie-Luis; Tophinke, Doris; Wever, Marcel Dominik; Hüllermeier, Eyke (Postersession Computerlinguistik der 40. Jahrestagung der Deutschen Gesellschaft für Sprachwissenschaft)

Enhanced Security of Attribute-Based Signatures - Blömer, Johannes; Eidens, Fabian; Juhnke, Jakob (The International Conference on Cryptology And Network Security (CANS))

Delegatable Attribute-based Anonymous Credentials from Dynamically Malleable Signatures - Blömer, Johannes; Bobolz, Jan (ACNS 2018 Applied Cryptography & Network security)
In this paper, we introduce the notion of delegatable attribute-based anonymous credentials (DAAC). Such systems offer fine-grained anonymous access control and they give the credential holder the ability to issue more restricted credentials to other users. In our model, credentials are parameterized with attributes that (1) express what the credential holder himself has been certified and (2) define which attributes he may issue to others. Furthermore, we present a practical construction of DAAC. For this construction, we deviate from the usual approach of embedding a certificate chain in the credential. Instead, we introduce a novel approach for which we identify a new primitive we call dynamically malleable signatures (DMS) as the main ingredient. This primitive may be of independent interest. We also give a first instantiation of DMS with efficient protocols.

Reciprocal effects between self-concept of ability and performance: A longitudinal study of children with learning disabilities in inclusive versus exclusive elementary education - Gorges, Julia; Neumann, Phillip; Wild, Elke; Stranghöner, Daniela; Lütje-Klose, Birgit (Learning and Individual Differences)
Ample empirical research from regular school settings documents reciprocal effects between academic performance and academic self-concept of ability (ASC), supporting what is known as a reciprocal effects model (REM). The present article investigates a REM in the domain of reading performance in a sample of elementary students with special educational needs in learning (SEN-L) who received special educational support in exclusive versus inclusive settings (N = 446). In exclusive settings, SEN-L students attend special schools and are completely separated from regular students. By contrast, SEN-L students in inclusive settings attend regular schools and are educated in classes with regular students. In both settings, SEN-L students are not graded and taught based on individual learning goals, which may affect reciprocal effects between ASC and reading performance. In addition, given that special education for SEN-L students relies heavily on individual reference standards to evaluate performance, we tested individual performance growth of SEN-L students as a predictor of ASC. Analyses of a longitudinal dataset across 3rd and 4th grade revealed some cross-lagged effects and an effect of performance growth on ASC in exclusive settings in particular. The discussion focuses on the role of individualized instruction, grades, peer groups, and individual versus social reference standards for reciprocal effects between ASC and performance as well as practical implications.
Keywords: BiLieF; Special educational needs; Learning disability; Academic selfconcept of ability; Reciprocal effects model; Inclusive education

Die Bielefelder Längsschnittstudie zum Lernen in inklusiven und exklusiven Förderarrangements (BiLieF) – Zentrale Befunde - Wild, Elke; Lütje-Klose, Birgit; Neumann, Phillip; Gorges, Julia (DDS – Die Deutsche Schule)
In der Bielefelder Längsschnittstudie zum Lernen in inklusiven und exklusiven Förderarrangements (BiLieF) wurden die psychosoziale und die Leistungsentwicklung bei Kindern mit sonderpädagogischem Förderbedarf im Förderschwerpunkt „Lernen“ von der 3. bis zur 5. Klasse in unterschiedlichen Fördersettings untersucht. Die Ergebnisse quantitativer und qualitativer Zugänge zeigen, dass vor allem proximale Faktoren auf der Ebene der Einzelschule – weniger die Form der Beschulung – für die Entwicklung der Kinder relevant sind.
Keywords: BiLieF; Inklusion; sonderpädagogischer Förderbedarf; Grundschule; Wohlbefinden; Rollenausprägungen sonderpädagogischer Lehrkräfte

ESPnet: End-to-End Speech Processing Toolkit - Watanabe, Shinji; Hori, Takaaki; Karita, Shigeki; Hayashi, Tomoki; Nishitoba, Jiro; Unno, Yuya; Enrique Yalta Soplin, Nelson; Heymann, Jahn; Wiesner, Matthew; Chen, Nanxin; Renduchintala, Adithya; Ochiai, Tsubasa (INTERSPEECH 2018, Hyderabad, India)
This paper introduces a new open source platform for end-toend speech processing named ESPnet. ESPnet mainly focuses on end-to-end automatic speech recognition (ASR), and adopts widely-used dynamic neural network toolkits, Chainer and Py-Torch, as a main deep learning engine. ESPnet also follows the Kaldi ASR toolkit style for data processing, feature extraction/format, and recipes to provide a complete setup for speech recognition and other speech processing experiments. This paper explains a major architecture of this software platform, several important functionalities, which differentiate ESPnet from other open source ASR toolkits, and experimental results with major ASR benchmarks.

Big Data-Kriege. Über Tötungslisten, Drohnen und die Politik der Datenbanken - Weber, Jutta (Machine Learning – Medien, Infrastrukturen und Technologien der Künstlichen Intelligenz)

Tagungsbericht: Kulturen der Moral – Moral Cultures. Internationale und interdisziplinäre Tagung in Kooperation mit der DGEJ vom 19. bis 22. September 2018 an der Universität Paderborn. - Becker, Rieke; Heidgen, Michael; Lauert, Markus; Witschel, Verena

Accreditation of X Qualities Instead of Quality X: A Normative Analysis of Criteria of the German Higher Education Accreditation Regime - Schneijderberg, Christian; Steinhardt, Isabel (Higher Education Policy)
This article examines the normative roots of criteria used for the accreditation of study programs in German higher education based on the orders of worth framework by Boltanski and Thévenot (On justification. Economies of worth, Princeton University Press, Princeton, 2006). From 1999 to 2017, the criteria have been subject to continuous efforts of legitimation, especially by the German Länder, which are in charge of public higher education in Germany. The empirical analysis shows that industrial (e.g., ‘standardization’), civic (e.g., ‘gender justice and equal opportunities’), and civic-industrial (e.g., ‘employability’) codings are the core of accreditation criteria. The normativity of these criteria constitutes accreditation as a technical arrangement running (a) a structural program (e.g., qualifications of academic teachers, modularization of study programs, and quality management) and (b) a political program (e.g., diversity of students and system of studies). Based on the empirical analysis, it is concluded that X does not stand for the accreditation of quality X. X stands for the accreditation of X qualities for specific normative purposes via the higher education accreditation regime.

Evaluating Innovative Measures in University Mathematics – The Case of Affective Outcomes in a Lecture focused on Problem-Solving - Kuklinski, Christiane; Leis, Elena; Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Neuhaus, Silke; Schaper, Niclas; Schürmann, Mirko (Proceedings of the Second Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2018, 5-7 April 2018))
The transition from high school to university mathematics has proven to be difficult for many students but especially for pre-service secondary teachers. To support these students at mastering this transition, various universities have introduced support measures of various kinds. The WiGeMath project developed a taxonomy that makes it possible to describe and compare these measures concerning their goals as well as their frame characteristics. We will exemplify the use of the taxonomy in the description of one specific innovative measure that was part of the WiGeMath evaluations. Moreover, we will present first results concerning the goal-fulfilment of this measure concerning affective characteristics of the student cohort and their predominant beliefs.
Keywords: Beliefs.; Motivational developments; Novel approaches to teaching; Teacher education; Transition to and across university mathematics

Körper, Materialitäten, Technologien

Degendering the Driver? Special Issue of ‚Transfers. International Journal for Mobility Studies‘, Vol. 8(1) (Transfers. International Journal for Mobility Studies)

Wer handelt mit unsichtbaren Schnittstellen? - Alpsancar, Suzana (Unterwachen und Schlafen. Anthropophile Medien nach dem Interface)

Quantitative Explanation as a Tight Coupling of Data, Model, and Theory - Krüger, Alexander; Tünnermann, Jan; Rohlfing, Katharina; Scharlau, Ingrid (Archives of Data Science, Series A)
What does it mean to explain data patterns? Cognitive psychologists and other scientists face this question when observable phenomena have to be explained in theoretical terms. Frequentist null-hypothesis testing – one prominent approach in psychology – controls error rates. Machine learning – an alternative prominent outside of, but not yet inside psychology – focuses on precise predictions. However, both alternatives often provide little insight into the data. We propose a combination of formal modeling and Bayesian statistical inference to ground explanations in data analysis. We support this approach by reference to philosophy of science and discussions of the current methods crisis in several empirical sciences and illustrate it with an example from visual attention research.

Die Ethik der Künstlichen Intelligenz - Alpsancar, Suzana (BTU News - September 2018)

Technikfolgenabschätzung als Zeitdiagnose - Alpsancar, Suzana (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Ropohl plädiert in seiner Technikphilosophie für eine bewusste Gestaltung des technischen Wandels, in dem auch die Ingenieur*innen in die Pflicht genommen werden. In meiner Rekonstruktion zeige ich, dass Ropohls normative Grundorientierung in einer Zeitdiagnose fußt, die er allerdings nicht expliziert. Aus seinem Beispiel ziehe ich die These, dass jeder Theorie der Technikfolgenabschätzung (TA) notwendig eine historisch-normative Signatur eingeschrieben ist. Um eine kritische Auseinandersetzung über das Selbstverständnis und den Zweck von TA zu führen, gilt es, anders als Ropohl, auch die inhärenten Zeitdiagnosen sichtbar zu machen und zu diskutieren.
Keywords: General Medicine

Modellbasierter Entwurf intelligenter mechatronischer Systeme mithilfe semantischer Technologien - Oestersötebier, Felix

On Efficiently Solvable Cases of Quantum k-SAT - Aldi, Marco; de Beaudrap, Niel; Gharibian, Sevag; Saeedi, Seyran (43rd International Symposium on Mathematical Foundations of Computer Science (MFCS 2018))
The constraint satisfaction problems k-SAT and Quantum k-SAT (k-QSAT) are canonical NP-complete and QMA_1-complete problems (for k >= 3), respectively, where QMA_1 is a quantum generalization of NP with one-sided error. Whereas k-SAT has been well-studied for special tractable cases, as well as from a parameterized complexity perspective, much less is known in similar settings for k-QSAT. Here, we study the open problem of computing satisfying assignments to k-QSAT instances which have a "matching" or "dimer covering"; this is an NP problem whose decision variant is trivial, but whose search complexity remains open. Our results fall into three directions, all of which relate to the "matching" setting: (1) We give a polynomial-time classical algorithm for k-QSAT when all qubits occur in at most two clauses. (2) We give a parameterized algorithm for k-QSAT instances from a certain non-trivial class, which allows us to obtain exponential speedups over brute force methods in some cases by reducing the problem to solving for a single root of a single univariate polynomial. (3) We conduct a structural graph theoretic study of 3-QSAT interaction graphs which have a "matching". We remark that the results of (2), in particular, introduce a number of new tools to the study of Quantum SAT, including graph theoretic concepts such as transfer filtrations and blow-ups from algebraic geometry; we hope these prove useful elsewhere.
Keywords: search complexity; local Hamiltonian; Quantum SAT; algebraic geometry

Quantum Generalizations of the Polynomial Hierarchy with Applications to QMA(2) - Gharibian, Sevag; Santha, Miklos; Sikora, Jamie; Sundaram, Aarthi; Yirka, Justin (43rd International Symposium on Mathematical Foundations of Computer Science (MFCS 2018))
The polynomial-time hierarchy (PH) has proven to be a powerful tool for providing separations in computational complexity theory (modulo standard conjectures such as PH does not collapse). Here, we study whether two quantum generalizations of PH can similarly prove separations in the quantum setting. The first generalization, QCPH, uses classical proofs, and the second, QPH, uses quantum proofs. For the former, we show quantum variants of the Karp-Lipton theorem and Toda's theorem. For the latter, we place its third level, Q Sigma_3, into NEXP using the Ellipsoid Method for efficiently solving semidefinite programs. These results yield two implications for QMA(2), the variant of Quantum Merlin-Arthur (QMA) with two unentangled proofs, a complexity class whose characterization has proven difficult. First, if QCPH=QPH (i.e., alternating quantifiers are sufficiently powerful so as to make classical and quantum proofs "equivalent"), then QMA(2) is in the Counting Hierarchy (specifically, in P^{PP^{PP}}). Second, unless QMA(2)= Q Sigma_3 (i.e., alternating quantifiers do not help in the presence of "unentanglement"), QMA(2) is strictly contained in NEXP.
Keywords: Complexity Theory; Quantum Computing; Polynomial Hierarchy; Semidefinite Programming; QMA(2); Quantum Complexity

The Complexity of Simulating Local Measurements on Quantum Systems - Gharibian, Sevag; Yirka, Justin (12th Conference on the Theory of Quantum Computation, Communication and Cryptography (TQC 2017))
An important task in quantum physics is the estimation of local quantities for ground states of local Hamiltonians. Recently, Ambainis defined the complexity class P^QMA[log], and motivated its study by showing that the physical task of estimating the expectation value of a local observable against the ground state of a local Hamiltonian is P^QMA[log]-complete. In this paper, we continue the study of P^QMA[log], obtaining the following results. The P^QMA[log]-completeness result of Ambainis requires O(log n)-local observ- ables and Hamiltonians. We show that simulating even a single qubit measurement on ground states of 5-local Hamiltonians is P^QMA[log]-complete, resolving an open question of Ambainis. We formalize the complexity theoretic study of estimating two-point correlation functions against ground states, and show that this task is similarly P^QMA[log]-complete. P^QMA[log] is thought of as "slightly harder" than QMA. We justify this formally by exploiting the hierarchical voting technique of Beigel, Hemachandra, and Wechsung to show P^QMA[log] \subseteq PP. This improves the containment QMA \subseteq PP from Kitaev and Watrous. A central theme of this work is the subtlety involved in the study of oracle classes in which the oracle solves a promise problem. In this vein, we identify a flaw in Ambainis' prior work regarding a P^UQMA[log]-hardness proof for estimating spectral gaps of local Hamiltonians. By introducing a "query validation" technique, we build on his prior work to obtain P^UQMA[log]-hardness for estimating spectral gaps under polynomial-time Turing reductions.
Keywords: Complexity theory; Quantum Merlin Arthur (QMA); local Hamiltonian; local measurement; spectral gap

Ground State Connectivity of Local Hamiltonians - Gharibian, Sevag; Sikora, Jamie (ACM Transactions on Computation Theory (TOCT))
Keywords: Local Hamiltonian; ground state connectivity; quantum Hamiltonian complexity; reconfiguration problem

The Online Advertising Tax. A Digital Policy Innovation. CAMRI Policy Briefs No. 1. (Short version) - Fuchs, Christian

The Online Advertising Tax as the Foundation of a Public Service Internet - Fuchs, Christian

Nationalism 2.0. The Making of Brexit on Social Media - Fuchs, Christian

Karl Marx @ 200. Debating Capitalism & Perspectives for the Future of Radical Theory - Fuchs, Christian; Monticelli, Lara (tripleC: Communication, Capitalism & Critique)

Karl Marx @ 200: Towards a Marxian Theory of Communication - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Racism, Nationalism and Right-Wing Extremism Online: The Austrian Presidential Election 2016 on Facebook - Fuchs, Christian (Critical Theory and Authoritarian Populism)

What would Marx have said about Facebook and Cambridge Analytica? - Fuchs, Christian (Monthly Review Online, November 28, 2018)

What Would Marx Have Said About Facebook and Cambridge Analytica? - Fuchs, Christian (openDemocracy)

Universal Alienation, Formal and Real Subsumption of Society Under Capital, Ongoing Primitive Accumulation by Dispossession: Reflections on the Marx@200-Contributions by David Harvey and Michael Hardt/Toni Negri - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Repeating Marx: Introduction to the Special Issue “Karl Marx @ 200: Debating Capitalism & Perspectives for the Future of Radical Theory“ - Fuchs, Christian; Monticelli, Lara (tripleC: Communication, Capitalism & Critique)

Reflections on Sven-Eric Liedman’s Marx-Biography “A World to Win: The Life and Works of Karl Marx” - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Postface: Horst Holzer’s “Communication & Society: A Critical Political Economy Perspective“ - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Karl Marx & Rosa Luxemburg: Postface to Rosa Luxemburg’s Article “Karl Marx” - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Marx’s Centenary (1918) in the Light of the Media and Socialist Thought - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

How Corbyn’s Plan to Tax Google and Facebook Could Create A Public Service Internet - Fuchs, Christian (Huffington Post UK)

Written Evidence Submitted to the House of Lords-Communications Select Committee Inquiry “The Internet: To Regulate Or Not To Regulate?“, Published on May 9, 2018 - Fuchs, Christian

Porous Aluminum Oxide and Magnesium Oxide Films Using Organic Hydrogels as Structure Matrices - Chen, Zimei; Kuckling, Dirk; Tiemann, Michael (Nanomaterials)
We describe the synthesis of mesoporous Al2O3 and MgO layers on silicon wafer substrates by using poly(dimethylacrylamide) hydrogels as porogenic matrices. Hydrogel films are prepared by spreading the polymer through spin-coating, followed by photo-cross-linking and anchoring to the substrate surface. The metal oxides are obtained by swelling the hydrogels in the respective metal nitrate solutions and subsequent thermal conversion. Combustion of the hydrogel results in mesoporous metal oxide layers with thicknesses in the μm range and high specific surface areas up to 558 m2∙g−1. Materials are characterized by SEM, FIB ablation, EDX, and Kr physisorption porosimetry.

Hydrogels as Porogens for Nanoporous Inorganic Materials - Weinberger, Christian; Kuckling, Dirk; Tiemann, Michael (Gels)
Organic polymer-hydrogels are known to be capable of directing the nucleation and growth of inorganic materials, such as silica, metal oxides, apatite or metal chalcogenides. This approach can be exploited in the synthesis of materials that exhibit defined nanoporosity. When the organic polymer-based hydrogel is incorporated in the inorganic product, a composite is formed from which the organic component may be selectively removed, yielding nanopores in the inorganic product. Such porogenic impact resembles the concept of using soft or hard templates for porous materials. This micro-review provides a survey of select examples from the literature.

Einleitung: Die „jüngere Queerfeminist*in“ spricht. - Degeling, Jasmin; Deuber-Mankowsky, Astrid; Horn, Sarah; Shnayien, Mary (onlinejournal kultur & geschlecht)

Teoria e análise do trabalho digital: Das cadeias globais de valor aos modos de produção (Translated by Rodrigo Moreno Marques) - Fuchs, Christian (Trabalho & Educação)

Media Theory, Public Relevance and the Propaganda Model - Klaehn, Jeffery; Broudy, Daniel; Fuchs, Christian; Godler, Yigal; Zollmann, Florian; Chomsky, Noam; Pedro-Carañana, Joan; Mills, Tom; Boyd-Barrett, Oliver (Media Theory)

The Rise of Authoritarian Capitalism - Fuchs, Christian (Global Dialogue)

Why There Are Certain Parallels Between Joachim C. Fest’s Hitler-Biography and Michael Wolff’s Trump-Book - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

How Can Creating A Public Service Internet Challenge the Power of Google and Facebook? - Fuchs, Christian (The Drum)

Digitale Demokratie und Öffentlich-Rechtliche Medien [Digital Democracy and Public Service Media] - Fuchs, Christian (ORF Public Value Studie 2017/2018: Der Auftrag: Demokratie [ORF Public Value Study 2017/2018: The Mission: Democracy])

Industry 4.0: The Digital German Ideology - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

netCommons Political and Ethical Guidelines for an Alternative Internet. EU Horizon 2020 Project netCommons, Deliverable 4.4 (December 2018) - Fuchs, Christian

Die Abschaffung der Netzneutralität, oder: Die Kolonialisierung digitaler Räume - Rolf, Carolin; Shnayien, Mary (onlinejournal kultur & geschlecht)
Mit der Abschaffung der Netzneutralität in den USA im Dezember 2017 wurden in der internationalen Debatte Interessenskonflikte bezüglich der Regulierung des Internets für eine breitere Öffentlichkeit sichtbar. Der Artikel gibt eine Einführung in die technischen Grundprinzipien des Internets und die Voraussetzungen von Netzneutralität und diskutiert auf dieser Basis verschiedene aktivistische Positionen anhand der Beispiele von queerem Aktivismus in den USA und dem Kampf für ein netzneutrales Internet in Indien, der unter dem Begriff des digitalen Kolonialismus geführt wird.

Populärkultur - Adelmann, Ralf (Von Automatismen bis Zersetzung. Wörterbuch-Projekt des Graduiertenkollegs Automatismen)

Methoden empirischer Bildungsforschung im Kontext Frühkindliche Bildung und Entwicklung

Weiblichkeit – Ansätze zur Theoretisierung.
Der Band will dazu beitragen, differenziertere Ansätze zum theoretischen Verständnis von Weiblichkeitskonstruktionen zu entwickeln. Die Beiträge diskutieren unterschiedliche Aspekte wie Diskurse über Weiblichkeit, Auseinandersetzungen mit analytischen Fassungen einer ‚hegemonialen Weiblichkeit‘, Brückenschläge zu leibtheoretischen Überlegungen, zum Spannungsfeld von Weiblichkeit und Mütterlichkeit sowie zur Rolle entsprechender Zuschreibungen in pädagogischen oder beraterischen Settings. Wie lässt sich über Weiblichkeit sprechen, wenn zugleich bezweifelt wird, ob es sie überhaupt gibt? Wenn die konstruktivistische Perspektive auf Geschlecht dieses als kontingente Zuschreibung definiert? Wenn in jedem Sprechen die Gefahr besteht, ungewollt vereindeutigende Zuschreibungen vorzunehmen und sie damit zu reifizieren? Das Anliegen des hier vorgelegten Bandes folgte vor allem aus der Feststellung, dass derzeit sehr viel über Männlichkeit und Väterlichkeit geforscht wird, aktuelle Arbeiten zum relationalen und begrifflichen Pendant Weiblichkeit jedoch weitgehend fehlen – und damit eine wesentliche Voraussetzung dafür, theoriegeleitete Überlegungen zu Geschlecht und Geschlechtervorstellungen weiter entwickeln zu können. Die in diesem Band versammelten Beiträge erhellen je unterschiedlich einzelne Aspekte dieser komplexen Zusammenhänge und tragen dazu bei, die diffus erscheinende Leerstelle im Wissen über aktuelle Weiblichkeitskonstruktionen sowohl mit feldspezifischen empiriebezogenen Analysen zu füllen als auch zu veranschaulichen, warum es aus einer Perspektive der Geschlechterforschung, die sich ihrerseits kritisch mit ihrer eigenen Wissensproduktion und den damit einhergehenden eigenen Entwürfen und Ausschlüssen auseinandersetzt, so schwierig scheint, ‚Weiblichkeit‘ als relevanten Forschungsgegenstand zu fassen. Die Beiträge diskutieren unterschiedliche Aspekte wie Diskurse über Weiblichkeit, Auseinandersetzungen mit analytischen Fassungen einer ‚hegemonialen Weiblichkeit‘, Brückenschläge zu leibtheoretischen Überlegungen, zum Spannungsfeld von Weiblichkeit und Mütterlichkeit sowie zur Rolle entsprechender Zuschreibungen in pädagogischen oder beraterischen Settings. Mit Beiträgen von Meike Baader, Astrid Messerschmidt, Arzu Cicek, Carrie Paechter, Melanie Kubandt, Maya Halatcheva-Trapp, Bastian Lasse, Frauke Grenz, Anna Orlikowski

Local intersections of Lagrangian manifolds correspond to catastrophe theory - Offen, Christian (arXiv:1811.10165)
Two smooth map germs are right-equivalent if and only if they generate two Lagrangian submanifolds in a cotangent bundle which have the same contact with the zero-section. In this paper we provide a reverse direction to this classical result of Golubitsky and Guillemin. Two Lagrangian submanifolds of a symplectic manifold have the same contact with a third Lagrangian submanifold if and only if the intersection problems correspond to stably right equivalent map germs. We, therefore, obtain a correspondence between local Lagrangian intersection problems and catastrophe theory while the classical version only captures tangential intersections. The correspondence is defined independently of any Lagrangian fibration of the ambient symplectic manifold, in contrast to other classical results. Moreover, we provide an extension of the correspondence to families of local Lagrangian intersection problems. This gives rise to a framework which allows a natural transportation of the notions of catastrophe theory such as stability, unfolding and (uni-)versality to the geometric setting such that we obtain a classification of families of local Lagrangian intersection problems. An application is the classification of Lagrangian boundary value problems for symplectic maps.

Hamiltonian boundary value problems, conformal symplectic symmetries, and conjugate loci - McLachlan, Robert I; Offen, Christian (New Zealand Journal of Mathematics)
In this paper we continue our study of bifurcations of solutions of boundary-value problems for symplectic maps arising as Hamiltonian diffeomorphisms. These have been shown to be connected to catastrophe theory via generating functions and ordinary and reversal phase space symmetries have been considered. Here we present a convenient, coordinate free framework to analyse separated Lagrangian boundary value problems which include classical Dirichlet, Neumann and Robin boundary value problems. The framework is then used to prove the existence of obstructions arising from conformal symplectic symmetries on the bifurcation behaviour of solutions to Hamiltonian boundary value problems. Under non-degeneracy conditions, a group action by conformal symplectic symmetries has the effect that the flow map cannot degenerate in a direction which is tangential to the action. This imposes restrictions on which singularities can occur in boundary value problems. Our results generalise classical results about conjugate loci on Riemannian manifolds to a large class of Hamiltonian boundary value problems with, for example, scaling symmetries.
Keywords: Hamiltonian boundary value problems; singularities; conformal symplectic geometry; catastrophe theory; conjugate loci

Front-End Processing for the CHiME-5 Dinner Party Scenario - Boeddeker, Christoph; Heitkaemper, Jens; Schmalenstroeer, Joerg; Drude, Lukas; Heymann, Jahn; Haeb-Umbach, Reinhold (Proc. CHiME 2018 Workshop on Speech Processing in Everyday Environments, Hyderabad, India)
This contribution presents a speech enhancement system for the CHiME-5 Dinner Party Scenario. The front-end employs multi-channel linear time-variant filtering and achieves its gains without the use of a neural network. We present an adaptation of blind source separation techniques to the CHiME-5 database which we call Guided Source Separation (GSS). Using the baseline acoustic and language model, the combination of Weighted Prediction Error based dereverberation, guided source separation, and beamforming reduces the WER by 10:54% (relative) for the single array track and by 21:12% (relative) on the multiple array track.

Discrimination of Stationary from Moving Targets with Recurrent Neural Networks in Automotive Radar - Grimm, Christopher; Breddermann, Tobias; Farhoud, Ridha; Fei, Tai; Warsitz, Ernst; Haeb-Umbach, Reinhold (International Conference on Microwaves for Intelligent Mobility (ICMIM) 2018)
In this paper, we present a neural network based classification algorithm for the discrimination of moving from stationary targets in the sight of an automotive radar sensor. Compared to existing algorithms, the proposed algorithm can take into account multiple local radar targets instead of performing classification inference on each target individually resulting in superior discrimination accuracy, especially suitable for non rigid objects, like pedestrians, which in general have a wide velocity spread when multiple targets are detected.

Full Bayesian Hidden Markov Model Variational Autoencoder for Acoustic Unit Discovery - Glarner, Thomas; Hanebrink, Patrick; Ebbers, Janek; Haeb-Umbach, Reinhold (INTERSPEECH 2018, Hyderabad, India)
The invention of the Variational Autoencoder enables the application of Neural Networks to a wide range of tasks in unsupervised learning, including the field of Acoustic Unit Discovery (AUD). The recently proposed Hidden Markov Model Variational Autoencoder (HMMVAE) allows a joint training of a neural network based feature extractor and a structured prior for the latent space given by a Hidden Markov Model. It has been shown that the HMMVAE significantly outperforms pure GMM-HMM based systems on the AUD task. However, the HMMVAE cannot autonomously infer the number of acoustic units and thus relies on the GMM-HMM system for initialization. This paper introduces the Bayesian Hidden Markov Model Variational Autoencoder (BHMMVAE) which solves these issues by embedding the HMMVAE in a Bayesian framework with a Dirichlet Process Prior for the distribution of the acoustic units, and diagonal or full-covariance Gaussians as emission distributions. Experiments on TIMIT and Xitsonga show that the BHMMVAE is able to autonomously infer a reasonable number of acoustic units, can be initialized without supervision by a GMM-HMM system, achieves computationally efficient stochastic variational inference by using natural gradient descent, and, additionally, improves the AUD performance over the HMMVAE.

Der ‚Verlust der natürlichen Selbstverständlichkeit‘ in Phänomenologie und Psychopathologie - Philippi, Martina (InterCultural Philosophy)
Die Habilitationsschrift des Psychopathologen Wolfgang Blankenburg thematisiert die ‚Grundstörung‘ in symptomarmen Schizophrenien, die das Korrelat zur ‚natürlichen Selbstverständlichkeit‘ des gesunden Lebensvollzugs darstellt. Für die Phänomenologie Husserlscher Provenienz ist diese von besonderer methodischer und inhaltlicher Bedeutung. Mein Beitrag zeigt auf, wie die Problematik der Selbstverständlichkeit als Kernthema von Husserls Phänomenologie gelesen werden kann, vor welche Herausforderungen sie sowohl die Phänomenologie als auch die Psychopathologie und Psychotherapie stellt und wie sich beide Ansätze wechselseitig befruchten können, d. h. wie durch eine Zusammenschau der Disziplinen die Phänomenologie mit anthropologisch-lebensweltlichen und die Psychopathologie und Psychotherapie um existenzielle Aspekten bereichert werden kann.
Keywords: Alltag; Wolfgang Blankenburg; Erkenntnistheorie; Edmund Husserl; Phänomenologie; Psychopathologie; Selbstverständlichkeit; Weltvertrauen

In depth Raman analysis of the ferroelectrics KTiOPO4 and LiNbO3: role of domain boundaries and defect - Rüsing, Michael
In the context of ferroelectrics spatially resolved Raman spectroscopy is a powerful tool to investigate stoichiometry, defects or the ferroelectric properties, as well as to visualize domain structures or waveguides. Using Raman spectroscopy for investigations requires a throughout understanding of the spectra and underlying mechanisms. For example, in the context of the common nonlinear materials, lithium niobate and potassium titanyl phosphate, no comprehensive understanding of the Raman spectra of the bulk materials is available, while the underlying mechanism of the domain wall contrast in Raman spectroscopy is not well understood. In this work, questions like these have been addressed in terms of systematic experimental investigations in close cooperation with density functional theory. In particular, it was possible to present a complete assignment of all phonons in the lithium niobate system, which serves as the basis for the understanding of the domain wall spectrum. Here, the domain wall spectrum can be explained with regard to microscopic structural effects, such as strains and electric fields, as well as a macroscopic change of selections rules. Both mechanisms are likewise present in the domain wall spectrum, while being present at different length scales. In the context of potassium titanyl phosphate the first throughout Raman investigations of domain structure, waveguides and periodically poled waveguides are presented. In the context of Rb-exchanged waveguides the change in stoichiometry, but also effects of strain are detected. Here, the Raman analysis provides a method to evaluate these effects.

Wortschatzerweiterung in autonomen Erwerbskontexten - Kilsbach, Sebastian

Efficient Sampling Rate Offset Compensation - An Overlap-Save Based Approach - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (26th European Signal Processing Conference (EUSIPCO 2018))
Distributed sensor data acquisition usually encompasses data sampling by the individual devices, where each of them has its own oscillator driving the local sampling process, resulting in slightly different sampling rates at the individual sensor nodes. Nevertheless, for certain downstream signal processing tasks it is important to compensate even for small sampling rate offsets. Aligning the sampling rates of oscillators which differ only by a few parts-per-million, is, however, challenging and quite different from traditional multirate signal processing tasks. In this paper we propose to transfer a precise but computationally demanding time domain approach, inspired by the Nyquist-Shannon sampling theorem, to an efficient frequency domain implementation. To this end a buffer control is employed which compensates for sampling offsets which are multiples of the sampling period, while a digital filter, realized by the wellknown Overlap-Save method, handles the fractional part of the sampling phase offset. With experiments on artificially misaligned data we investigate the parametrization, the efficiency, and the induced distortions of the proposed resampling method. It is shown that a favorable compromise between residual distortion and computational complexity is achieved, compared to other sampling rate offset compensation techniques.

The RWTH/UPB System Combination for the CHiME 2018 Workshop - Kitza, Markus; Michel, Wilfried; Boeddeker, Christoph; Heitkaemper, Jens; Menne, Tobias; Schlüter, Ralf; Ney, Hermann; Schmalenstroeer, Joerg; Drude, Lukas; Heymann, Jahn; Haeb-Umbach, Reinhold (Proc. CHiME 2018 Workshop on Speech Processing in Everyday Environments, Hyderabad, India)
This paper describes the systems for the single-array track and the multiple-array track of the 5th CHiME Challenge. The final system is a combination of multiple systems, using Confusion Network Combination (CNC). The different systems presented here are utilizing different front-ends and training sets for a Bidirectional Long Short-Term Memory (BLSTM) Acoustic Model (AM). The front-end was replaced by enhancements provided by Paderborn University [1]. The back-end has been implemented using RASR [2] and RETURNN [3]. Additionally, a system combination including the hypothesis word graphs from the system of the submission [1] has been performed, which results in the final best system.

Benchmarking Neural Network Architectures for Acoustic Sensor Networks - Ebbers, Janek; Heitkaemper, Jens; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (ITG 2018, Oldenburg, Germany)
Due to their distributed nature wireless acoustic sensor networks offer great potential for improved signal acquisition, processing and classification for applications such as monitoring and surveillance, home automation, or hands-free telecommunication. To reduce the communication demand with a central server and to raise the privacy level it is desirable to perform processing at node level. The limited processing and memory capabilities on a sensor node, however, stand in contrast to the compute and memory intensive deep learning algorithms used in modern speech and audio processing. In this work, we perform benchmarking of commonly used convolutional and recurrent neural network architectures on a Raspberry Pi based acoustic sensor node. We show that it is possible to run medium-sized neural network topologies used for speech enhancement and speech recognition in real time. For acoustic event recognition, where predictions in a lower temporal resolution are sufficient, it is even possible to run current state-of-the-art deep convolutional models with a real-time-factor of 0:11.

Insights into the Interplay of Sampling Rate Offsets and MVDR Beamforming - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (ITG 2018, Oldenburg, Germany)
It has been experimentally verified that sampling rate offsets (SROs) between the input channels of an acoustic beamformer have a detrimental effect on the achievable SNR gains. In this paper we derive an analytic model to study the impact of SRO on the estimation of the spatial noise covariance matrix used in MVDR beamforming. It is shown that a perfect compensation of the SRO is impossible if the noise covariance matrix is estimated by time averaging, even if the SRO is perfectly known. The SRO should therefore be compensated for prior to beamformer coefficient estimation. We present a novel scheme where SRO compensation and beamforming closely interact, saving some computational effort compared to separate SRO adjustment followed by acoustic beamforming.

New Quick And Easy Publication - Will be edited by LibreCat team - Taschl-Erber, Andrea (Quick And Easy Journal Title)

Blue Blood in the Red? Nobles on the Antwerp annuity market (1490-1493) - Huybrechts, Yves; Buylaert, Frederik (EDAD MEDIA: Revista de Historia)

Astronomie in der Lehrerausbildung - Hohmann, Sascha; Quast, Martin (PhyDid B)

Reziprozität zwischen Lehrenden und Studierenden als Kern der Kompetenzorientierung – eine didaktisch-praktische Anwendung - Hoyer, Isabelle; Corves, Annette; Nyquist, Elin; Reis, Oliver (Neues Handbuch Hochschullehre)

Reziprozität zwischen Lehrenden und Studierenden als Kern der Kompetenzorientierung – eine Grundsatzklärung - Hoyer, Isabelle; Corves, Annette; Nyquist, Elin; Reis, Oliver (Neues Handbuch Hochschullehre)

Phänomenologie und Philosophiedidaktik - Albus, Vanessa; Philipp, Thomas (Zeitschrift für Didaktik der Philosophie und Ethik)

Konzeption von fachmathematischen Schnittstellenmodulen für Lehramtsstudierende am Beispiel ausgewählter Themen der höheren Analysis. - Hoffmann, Max

Chor-Individuen. Anmerkungen zur ‚realistisch‘ bewegten Chordramaturgie in Les Huguenots und Le Prophète - Münzmay, Andreas (Bild und Bewegung im Musiktheater. Interdisziplinäre Studien im Umfeld der Grand Opéra / Image and Movement in Music Theatre. Interdisciplinary Studies around Grand Opéra)
Wie versetzen Eugène Scribe und Giacomo Meyerbeer den Chor auf der Opernbühne in Bewegung – in innere Bewegung, und ebenso in äußere –, so dass diese Bewegung spontan und ›realistisch‹ erscheint? Ausgehend von einigen allgemeinen Thesen zur Musikdramaturgie Scribe’scher Grands opéras will die vorliegende Lektüre von Libretti, Partituren und livrets de mise en scène einige Schlaglichter auf prominente Momente der Gruppen- und Chordramaturgie in Les Huguenots und Le Prophète werfen. Stärker als bislang üblich soll dabei auch die zentrale Rolle der Librettistik herausgestellt werden, die insbesondere im Bereich der Exposition und dramaturgischen Führung der Nebenrollen entscheidende Voraussetzungen schafft. Zudem soll die gängige Lesart, wonach Meyerbeers Chordramaturgie im Kern eine Dramaturgie der ›Massen‹ sei, differenziert und in bestimmter Hinsicht auch relativiert werden. Die Ensemble- und Chordramaturgien in Les Huguenots und Le Prophéte können gleichermaßen als Beispiele der eingangs umrissenen Scribe’schen dramaturgischen Grundtechnik gelesen werden, die darauf beruht, die Verständnisgrundlagen der Stücke vollständig und lückenlos im Inneren der Stücke selbst zu vermitteln. (Es gibt nichts, was man schon vorher über Hugenotten oder Anabaptisten wissen müsste, um die Intrigen von Les Huguenots bzw. Le Prophète in allen Details zu verstehen.) Die Verfahren einer ›realistischen‹ Chordramaturgie mithilfe einer Vielzahl librettistisch bereitgestellter Nebenrollen, die als ›Chor-Individuen‹ selbst die ›Massen‹-Chöre gleichsam als maximierte Ensembles konfigurieren und dadurch von Innen heraus plausibilisieren, haben genau in diesem Zusammenhang in beiden Werken eine tragende Funktion: Gerade diese beiden Werke setzen eine Dynamik der ›Massen‹ nicht etwa einfach als Zeitphänomene und allgemeine Erfahrung voraus, sondern lassen im Gegenteil mit großer (musik)dramaturgischer Präzision das Wirken von ›Massen‹ als Folge des Handelns von lauter Individuen erscheinen.

Der FID Musikwissenschaft (Musiconn) in Lehre und Forschung. Kommentar aus Nutzer-Perspektive - Münzmay, Andreas (Zeitschrift für Bibliothekswesen und Bibliographie (ZfBB))
Keywords: Library and Information Sciences

Virtualitäten der Opéra comique und XML-Kode als ‚Teleskop‘ - Münzmay, Andreas (Symposiumsbericht ‚Virtualitäten des Barock. Deleuze und musikalische Analyse‘)
Die französische Opéra comique in ihrer Umbruchphase nach 1750 kann im Sinne Gilles Deleuzes als idealtypisch ›barock‹ begriffen werden. Die vermeintlich simplen musikalischen Oberflächen, auf die Analyse in den unzähligen Opéras comiques des 18. Jahrhunderts immer dann trifft, wenn Melodiezitate im Spiel sind, sind dabei integraler Teil eines komplexen wissenskulturellen Systems. Können die Begriffe der »Falte« und der »Virtualität« eine poststrukturalistisch inspirierte Analyse befördern, die an das Hypertextualitätskonzept, wie es Gérard Genette 1982 mit Palimpsestes: La littérature au second degré so griffig systematisiert hat, anschließt, aber auch darüber hinaus geht? Um diese Frage soll es im ersten Teil des vorliegenden Versuchs gehen. Im zweiten Teil soll überlegt werden, auf welche spezifische Weise XML-Codierung (als Kernverfahren digitaler Edition) und analytische Erkenntnismöglichkeiten interagieren. Anlass und Materialbasis für einen solchen Ausblick auf digitale Editionsmethoden soll die 2016 erschienene digitale Edition des Werks Annette et Lubin von Justine Favart sein, die in etwa sechsjähriger Arbeit im Frankfurter Akademienprojekt OPERA – Spektrum des europäischen Musiktheaters. Historisch-kritische Hybridausgaben erarbeitet werden konnte.

Lesen und Schreiben im digitalen Dickicht. Musikwissenschaft, Digital Humanities und die hybride Musikbibliothek - Münzmay, Andreas (Bibliothek: Forschung und Praxis)
Digitalisierung generiert ‚hybride‘ Objekte, die zwar als digitale Datei lesbar und manipulierbar sind, das zugrundeliegende kulturhistorische Objekt jedoch weiterhin ‚enthalten‘. Eine Bibliothek, die Objekte aus ihren Beständen digitalisiert, begründet also eigentlich keine sog. digitale Bibliothek, sondern eine hybride Bibliothek. Im Falle musikalischer Überlieferung ist die Sachlage aufgrund der medienhistorischen Komplexität musikalischer Artefakte besonders unübersichtlich. Verschärft wird die heutige Situation noch durch die Erzeugnisse der Digital Humanities, die keineswegs bloß ‚Informationen‘ sind, sondern ihrerseits komplexe und in der Regel hybride Textgebilde, die häufig komplette digitalisierte Re-Publikationen von Kulturobjekten einbinden, die digital ‚beschriftet‘ und vernetzt werden. Das digitale ‚Dickicht‘ erfordert einen gleichsam genetischen und relationalen Katalog, in dem die konkreten kulturhistorischen Objekte in ihren konkreten Sammlungskontexten – also als Unikate – Ankerfunktion haben. Der Essay geht zurück auf einen Vortrag bei der AIBM-Jahrestagung, Symposium der AG Musikabteilungen an wissenschaftlichen Bibliotheken, Detmold, 8. September 2016.

Boundary Values of Eigenfunctions on Riemannian Symmetric Spaces - Hilgert, Joachim; Hansen, S.; Parthasarathy, A.

,Queer‘ aufs Spiel gesetzt: Über Beißreflexe, queere Bewegungsgeschichte und gegenwärtige Affektkulturen. (Best Publication Award Gender&Medien 2019) - Degeling, Jasmin; Horn, Sarah (onlinejournal kultur&geschlecht 21)

Rezension zu: Yost, Jeffrey R.: Making IT Work. A History of the Computer Services Industry. Cambridge 2017 - Schmitt, Martin (H-Soz-Kult)

Rezension zu „Vaterunser. Das Gebet Jesu neu gelesen“ (2018) von Papst Franziskus mit Marco Pozza - Breckner, Anne (Blog des Instituts für Evangelische Theologie an der Universität Paderborn)

Einfach frei Schnauze. Religiöse Parodien der Reformationszeit - Breckner, Anne (TheoMag. Tà katoptrizómena. Das Magazin für Kunst – Kultur – Theologie – Ästhetik)

Vernetzte Bankenwelt. Computerisierung in der Kreditwirtschaft der Bundesrepublik und der DDR - Schmitt, Martin (Wege in die digitale Gesellschaft. Computernutzung in der Bundesrepublik 1955-1990)

Über Mehrsprachigkeit und Migration nachdenken und sprechen. Migrationspädagogische Perspektiven auf den Einsatz sog. Migrationsliteratur im Deutschunterricht - Büttner, Denise